KUALITAS PELAYANAN JAMINAN KESEHATAN MELALUI SISTEM INFORMASI PELAYANAN JAMINAN KESEHATAN DAFTAR DI TEMPAT (SIPAJAKDADI) DI KABUPATEN SUMEDANG - Rohmanudin, Ade Opik; Yadi, Agus Fitri; Putra, Mahesa Dwi; Puspayani, Puja; Melani, Putri; Maeni, Ristia Nur (LPPM UNSAP & FISIP UNSAP, 2024)
The aim of this research is to determine the quality of health insurance services through the SIPAJAKDADI website (on-site payment health insurance service information system) in the Sumedang district social service. The method used in this research is qualitative method. Determining informants in this research used purposive sampling. There were 3 informants, namely the field secretary, field staff, and operators from SIPAJAKDADI. Data collection techniques were carried out through literature studies and field studies consisting of observation, in-depth interviews, documentation and triangulation. Data processing procedures are: data reduction, data display, and conclusion drawing/verification.The results of the research show that health insurance services through sipajakdadi in the Sumedang district social service have been implemented quite well, this is because there are obstacles in the implementation facilities such as computers and networks, where there are still several villages in Sumedang district where the internet network cannot be fully reached and there are also some have inadequate computers. Efforts made to overcome the above obstacles are by expanding the internet network throughout the Sumedang district and upgrading computers to newer ones. In connection with the above conclusions, the researcher provides suggestions for the Sumedang Regency Social Service to improve internet network infrastructure in each village, including the application of the latest technology to ensure stabel and even connectivity throughout the Sumedang Regency village area. Improve and expand computer facilities in each village taking into account specific needs and ensuring wider access to technology.